Hypothalamic-Pituitary Diseases (Endocrinology,, 2018)
This book presents the state of the art in the pathophysiology, diagnosis, and therapy of hypothalamic and pituitary disorders. After an introduction devoted to the physiology of the neuroendocrine control of the hypothalamic-pituitary unit, the diverse disorders involving hormonal excess or deficiency are systematically addressed axis by axis. For each disorder, pathophysiology, clinical presentation, and management are discussed in detail. In addition, individual chapters focus on the neuroendocrinology of energy homeostasis and of bone metabolism, metabolic derangement secondary to pituitary dysfunction, and pituitary control of the endocrine pancreas. While the focus of the book is predominantly on pathophysiological and clinical aspects, due attention is also devoted to potential diagnostic and therapeutic innovations. The book is intended as a major reference for endocrinologists and basic and clinical scientists. .